2016
DOI: 10.1152/japplphysiol.00841.2015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term exposure to head-down tilt on cerebral hemodynamics: a prospective evaluation of a spaceflight analog using phase-contrast MRI

Abstract: This is the first study to examine cerebral hemodynamics using phase-contrast MRI during various angles of head-down tilt. Furthermore, the study investigated the additional effects of increased ambient carbon dioxide during head-down tilt as an analog to the environment onboard the International Space Station.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
62
3
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 43 publications
10
62
3
4
Order By: Relevance
“…Thus, the venous system played a major role in the compensation for the increase in PG immediately after a change in posture to the HDT, ie, the sudden change in intracranial condition. In contrast to our results, a previous study showed that venous outflow of the IJVs was decreased after 4.5 hours in the –12° HDT . This discrepancy indicates the importance of a time‐dependency effect of the HDT.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Thus, the venous system played a major role in the compensation for the increase in PG immediately after a change in posture to the HDT, ie, the sudden change in intracranial condition. In contrast to our results, a previous study showed that venous outflow of the IJVs was decreased after 4.5 hours in the –12° HDT . This discrepancy indicates the importance of a time‐dependency effect of the HDT.…”
Section: Discussionsupporting
confidence: 93%
“…The loading induced by lowering the head did not exceed the intracranial compensatory faculties, due to the low tilt angle and extremely short duration exposure. In contrast to our results, a recent report documented that the CBF and the venous outflow of the IJVs were decreased after 4.5 hours in a –6° HDT . According to these results, the duration of the posture may be a profound factor when investigating the effects of a low‐angle HDT on the intracranial condition.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Likewise terrestrial head down studies with and without hypercapnia have demonstrated increased retinal nerve fiber layer on OCT and might still prove to be a suitable terrestrial analog to test hypotheses and potential countermeasures to SANS. [73][74][75][76][77][78][79][80][81][82] These countermeasures include metabolic and pharmacologic treatments 69,[83][84][85][86][87] in the one carbon pathways; 63,69 lower body negative pressure; [74][75][76] and swim goggles to affect the translaminar pressure gradient. While current data does not seem to support prolonged, significant elevations of ICP to the levels seen in IIH, throughout LDSF, Lawley et al proposed that even mild elevations of ICP for a prolonged duration may contribute to the structural changes seen in SANS.…”
Section: Oct and Sansmentioning
confidence: 99%